EFEKTIVITAS PENERAPAN EKOSISTEM HALAL VALUE CHAIN (HVC) PADA INDUSTRI MAKANAN DAN MINUMAN HALAL DI INDONESIA - Charina, Anne; Charisma, Dinna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Indonesia's potential in the halal industry is currently very calculated, because Indonesia is a country with the largest Muslim population in the world. This role should not only be seen as a mere captive market but must also encourage the growth of the halal industry in Indonesia which is able to compete globally. However, currently the Indonesian halal food and beverage industry is not yet included in the top 10 countries with the best performance in the world for halal food and beverages. Whereas on the other hand, Indonesia actually has a great opportunity to develop halal products in this sector. The purpose of this study is to determine the effectiveness of implementing the halal value chain (HVC) ecosystem in the halal food and beverage industry in Indonesia. This research method uses a type of qualitative research with a descriptive analysis approach. Data collection techniques were carried out by observation and literature study. The results of this study indicate that based on data from the Central Statistics Agency (BPS) regarding the Data on the Number of Exports of Halal Food and Beverages for 2022 after the implementation of HVC shows that there has been an increase in the export process and a reduction in the import process; this means that the application of HVC to halal food and beverages in Indonesia is very influential so that it can increase the effectiveness of these halal products even though they are not fully running optimally. The supporting factors for the success of HVC are government support, halal assets, information technology, human resource management, collaborative partnerships, halal certification and halal traceability.